ASSESSMENT OF THE ECOLOGICAL STATE OF RURAL SETTLEMENTS BY INDICATORS OF DRINKING WATER QUALITY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Ruslana Valerko; Liudmyla Herasymchuk; Iryna Patseva; Bogdan Gnatuk (Environmental Problems)
The purpose of the study was to assess the state of ecological development of rural rural areas of the amalgamated territorial communities of Zhytomyr district based on drinking water quality indicators of non-centralised water supplysources to ensure their sustainable development.It was found that the average pH value was within the current standard, which indicates an excellent environmental condition for thisindicator. The average content of nitrates in drinking water, which in all the studied communities exceeded the standard by 1.4 to 3.5 times, was assessed at only one point. The averageconcentration of total iron exceeded the current standard by 1.9 times only in the rural settlements of the Liubar community. Satisfactory water quality, in terms of total iron content, was recorded in 50 per cent of the surveyed communities. In 70 per cent of the studied communities, the average value of total hardness was recorded at a level higher than 7.0 mmol/dm3, which indicates, according to European legislation, a poor condition of drinking water.Thus, having assessed the ecological state of rural areas in terms of drinking water quality, it was found that most of the studied communities have a satisfactory state of the territories, as the total number of points varied between 2.25–3.3 points. And the greatest contribution to the decline in the level of environmental developmentof rural settlements is made by the indicators of nitrate content in drinking water and its hardness.